The Effectiveness of AVAZ AAC Media in Improving the Expressive Language Skills of Children with Down Syndrome in Surakarta City - Tomas Kurnia Adi; Dian Atnantomi Wiliyanto; Alfiani Vivi Sutanto (Teknodika, 2026)
Down Syndrome causes intellectual disabilities and language delays, especially expressive language. Children with Down Syndrome require concrete and easy-to-understand learning media. Augmentative and Alternative Communication (AAC), specifically AVAZ AAC. This media has features that can offer effective support. This study aims to analyze the effectiveness of AVAZ AAC in improving the expressive language skills of children with Down Syndrome in Surakarta. This research is a quantitative descriptive study with a quasi-experimental design using a one-group pre-test–post-test approach on 10 children with Down Syndrome who were selected purposively. The intervention consisted of 6 sessions. Expressive language skills were measured using the NSST. Data were analyzed using a Paired t-test and Cohen's d effect size. The average score increased from 6 to 16.3, with a change in category from entirely low to mostly moderate. The Paired T-Test produced p = 0.001, and effectiveness was declared strong with an effect size of Cohen's d = 1.43, indicating a significant influence of AVAZ AAC media. The use of AVAZ AAC media has been proven effective in improving the expressive language skills of children with Down Syndrome, as evidenced by changes in score categories, a p-value of 0.001, and a large effect size (d = 1.43). This media is recommended for continued use by parents, teachers, schools, and therapists, and supported by ongoing research with a larger sample size and extended duration.